Managerial Communication and Decision Making in Banking Sector of Kathmandu Valley (Economic Journal of Nepal, 2022)
This study aims to determine the influence of managerial communication in decision making of banking sector in Kathmandu Valley. Managerial communication has long been a hot issue in the business world since no company can survive without effective communication with its stakeholders. Similarly, decision making is considered as an essential management function since it is a normal task for every manager and the quality of decision influences the existence of organization. The study found that managerial communication could help a lot in decision making and that enhance organizational creativity in its practice and thereby increase in its level of performance. The managerial communication has a positive and significant influence on decision making of banking sector. This study concluded that managerial communication has been one of the important issues in decision making that could result higher performance and higher productivity of an organization.